Drug discovery and target validation in the p53 pathway - Lane, David (Henry Stewart Talks, 2009)
Controlling cancer, p53 discovery, Oncoproteins, SV40, Adeno and HPV, The p53 protein, Incidence of genetic changes in p53 in human cancers, What does p53 do?, The p53 pathway is blocked in many tumor cells, p53 and HDM2 are connected by a negative feedback loop, Mdm2 controls p53, Evidence for the fine regulation of the p53 response, How does p53 cause advanced aging?, Therapy approaches, Gene therapy, Activating p53, Targets for p53 activation, Small peptides block p53/HDM interaction and activate p53, Peptide minimization and optimization, Nutlin 3 specificity, Thousands of compounds can be tested for their ability to activate p53-dependent transcription, CYC202: a cdk inhibitor in clinical trial that is a non genotoxic activator of the p53 response, CDK inhibition, Regulation of p53 by ubiquitin like proteins, Stress stimuli that control the activity of p53, New isoforms of p53